THINK TALK WRITE SEBAGAI UPAYA MENINGKATKAN KOMUNIKASI MATEMATIS SISWA - Pipit Retnowati; Arta Ekayanti (Prodi Pendidikan Matematika FKIP Universitas Madura, 2020)
Mathematical communication is the ability of students to explain an idea from the results of thinking with pictures, diagrams, or mathematical symbols verbally or in writing, so mathematical communication is very important for students to have. Among the learning models that can be applied in the learning process are Think Talk Write (TTW) learning models. By implementing Think Talk Write (TTW) students are expected to be able to practice their mathematical communication skills both orally and in writing. Based on the steps of Think Talk Write (TTW) namely thinking, speaking and writing it is very possible to improve students' mathematical communication skills. Because in the Think Talk Write (TTW) learning model students are trained to think independently of various learning sources. Steps of Think Talk Write (TTW) also trains students to speak to convey ideas from the ideas that have been found and to obtain the results of the discussion in their own language. Both of these steps accustom students to practice mathematical communication skills of students both verbally and in writing